2015
DOI: 10.4103/0973-1296.172961
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive extract from moringa oleifera inhibits the pro-inflammatory mediators in lipopolysaccharide stimulated macrophages

Abstract: Introduction:Inflammation is a well-known physiological response to protect the body against infection and restore tissue injury. Nevertheless, the chronic inflammation can trigger various inflammatory associated diseases/disorder. Moringa oleifera is a widely grown plant in most tropical countries and it has been recognized traditionally for several medicinal benefits.Objectives:The objective of this study was to investigate the anti-inflammatory properties of M. oleifera extract on lipopolysaccharide (LPS) -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…These findings indicate that M. oleifera effectively suppressed the production of inflammatory mediators such as NO, proinflammatory cytokines (IL-6, IL-1 β , and TNF- α ), and PGE2. It has also reduced the expression of inflammatory markers which include NF- κ B, iNOS, and COX-2 [ 48 , 80 83 ]. These findings have suggested that the edible part of M. oleifera may act as an effective natural anti-inflammatory remedy against inflammatory associated diseases.…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…These findings indicate that M. oleifera effectively suppressed the production of inflammatory mediators such as NO, proinflammatory cytokines (IL-6, IL-1 β , and TNF- α ), and PGE2. It has also reduced the expression of inflammatory markers which include NF- κ B, iNOS, and COX-2 [ 48 , 80 83 ]. These findings have suggested that the edible part of M. oleifera may act as an effective natural anti-inflammatory remedy against inflammatory associated diseases.…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…Furthermore, previous studies have documented that M. oleifera can selectively inhibit the production of iNOS and COX-2 and significantly inhibit the secretion of NO and other inflammatory markers—including PGE-2, TNF-α, IL-6, and IL-1β—in lipopolysaccharide (LPS)-induced RAW264.7 cells. Meanwhile, it can induce the production of IL-10 in LPS-stimulated macrophages in a dose-dependent manner, thereby contributing to the suppression of NF-κB signaling pathway [ 19 , 20 ]. The novel bioactive phenolic glycosides 4-[(2- O -acetyl-α- l -rhamnosyloxy)benzyl] isothiocyanate (RBITC) from M. oleifera inhibited expression of COX-2 and iNOS at both the protein and mRNA levels through inhibiting major upstream signaling pathways mitogen-activated protein kinases (MAPKs) and NF-κB [ 21 ].…”
Section: Anti-inflammationmentioning
confidence: 99%
“…Extracts from M. oleifera display multiple pharmacological activities, including anti-inflammatory [ 31 , 32 , 33 , 34 ], antibacterial [ 35 ], antioxidant [ 36 ], anti-cancer [ 37 ], hepatoprotective [ 38 , 39 ] and neuroprotective [ 40 , 41 , 42 ] activities. The leaves and fruits also possess hypocholesterolaemic activity in Wistar rats [ 43 ] and rabbits [ 44 ].…”
Section: Introductionmentioning
confidence: 99%